ANALYSIS OF STUDENT ERRORS IN QUADRATE FUNCTION MATERIALS BASED ON NEWMAN PROCEDURE - Rheta Puspita Sari (Jurnal Prinsip Pendidikan Matematika, 2021)
This study aims to determine the types of student errors and the causes of student errors in solving quadratic function questions based on the Newman procedure at MTs Nurul Yaqin Pekanbaru based on Newman procedures. This type of research is descriptive qualitative. The subjects in this study were 13 students of class IX MTs Nurul Yaqin Pekanbaru. The data were collected using the written test method given to students. The results showed the percentage of errors made by students in solving math problems related to the quadratic function material based on the Newman procedure were: (a) the percentage of reading errors made by students was 7.6%, (b) the percentage of misunderstanding was 35.38%, (c) the percentage of transformation errors is 40%, (d) the percentage of errors in processing skills is 35.38%, and (e) the percentage of errors in writing the final answer is 56.92%. The causes of student errors include rushing in reading questions and lack of knowledge of symbol, symbols contained in math problems, not having the ability to write down what is known and what is asked in the questions correctly, not mastering rectangular and square material, lacking practicing doing practice questions related to quadratic functions, not understanding the formulas that should be used, not being careful in carrying out the calculation process, carelessly working on questions, the result of previous mistakes, inability to determine units, not being used to writing conclusions, rushing to do it completion process.